2008
DOI: 10.1097/meg.0b013e3282f5f5d5
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related fluorodeoxyglucose uptake in acute radiation-induced hepatitis

Abstract: Therapeutic assessment with fluorine-18 fluorodeoxyglucose (FDG) positron emission tomography (PET) is sometimes problematic after radiation therapy. Herein we describe a patient with acute radiation-induced hepatitis in which PET showed dose-dependent FDG uptake. A 50-year-old man underwent FDG PET for staging of esophageal cancer. Chemoradiotherapy was delivered concurrently with a radiation field that expanded from the esophagus into the upper stomach to cover metastasis of the gastric wall. The patient als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…[57] Nakahara et al reported a case of FDG uptake in the left lobe of liver 28 days after completion of radiation for esophageal cancer, with resolution on follow-up PET scan 3 months later, consistent with our cases. [8] In our series, we found FDG uptake within 34 and 42 days postradiation. Interestingly, among the remaining 62 patients in our database, hepatic FDG-uptake was not observed, suggesting that intrinsic biologic features in addition to treatment and imaging timing may play a role.…”
Section: Discussionsupporting
confidence: 52%
“…[57] Nakahara et al reported a case of FDG uptake in the left lobe of liver 28 days after completion of radiation for esophageal cancer, with resolution on follow-up PET scan 3 months later, consistent with our cases. [8] In our series, we found FDG uptake within 34 and 42 days postradiation. Interestingly, among the remaining 62 patients in our database, hepatic FDG-uptake was not observed, suggesting that intrinsic biologic features in addition to treatment and imaging timing may play a role.…”
Section: Discussionsupporting
confidence: 52%
“…In one study it was shown that up to 35% of patients with esophageal cancer will develop liver metastases [29]. In addition to metastatic disease, the liver is also particularly prone to radiation-induced liver disease during radiotherapy of distal esophageal cancer, due to the close proximity of the left lobe which is accordingly included in the standard radiation field [2729].…”
Section: Discussionmentioning
confidence: 99%
“…In one study it was shown that up to 35% of patients with esophageal cancer will develop liver metastases [29]. In addition to metastatic disease, the liver is also particularly prone to radiation-induced liver disease during radiotherapy of distal esophageal cancer, due to the close proximity of the left lobe which is accordingly included in the standard radiation field [2729]. Given that serial PET/CT is increasingly performed during neoadjuvant chemoradiation of esophageal cancer and that both metastases and radiation-induced liver disease may manifest as increased foci of FDG avidity at PET scanning, our study provides important results that address how these two entities might be distinguished.…”
Section: Discussionmentioning
confidence: 99%
“…Common sites of metastatic spread in esophageal cancer include the abdominal lymph nodes, liver, and lungs [10]. In one study, it was revealed that up to 35% of patients with esophageal cancer will develop liver metastases [11]. In addition to metastatic disease, the liver is also particularly prone to radiation-induced liver disease (RILD) during RT for distal esophageal cancer, owing to its close proximity to the left lobe, which is accordingly included in the standard radiation field [11].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, it was revealed that up to 35% of patients with esophageal cancer will develop liver metastases [11]. In addition to metastatic disease, the liver is also particularly prone to radiation-induced liver disease (RILD) during RT for distal esophageal cancer, owing to its close proximity to the left lobe, which is accordingly included in the standard radiation field [11]. When a patient displays FDG activity in the left or caudate liver lobes after CRT, a more detailed investigation should be performed in order to confirm or exclude distant metastases [12].…”
Section: Discussionmentioning
confidence: 99%